2017
DOI: 10.22603/ssrr.1.2016-0012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of duloxetine on neuropathic pain in patients intolerant to continuous administration of pregabalin

Abstract: Abstract:Purpose: We examined duloxetine's effectiveness in the treatment of neuropathic pain in patients who were intolerant to continuous pregabalin administration. Materials and Methods: The present study is a retrospective study of patients diagnosed with neuropathic pain with neuropathic leg pain as the chief complaint. We analyzed 20 cases in which pregabalin was changed to duloxetine because of adverse effects (16 cases) or treatment failure (4 cases). The incidence of adverse events after duloxetine ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…These AEs can significantly lower compliance, sometimes leading to discontinuation before a therapeutic effect can be achieved. In patients in whom insufficient efficacy is observed with pregabalin, switching to other agents has been studied, and a reduction in AEs and an improvement in pain relief have been reported [12]. Thus, when considering a switch from pregabalin to mirogabalin, safety is an important consideration; however, there are insufficient safety data available in this setting.…”
Section: Introductionmentioning
confidence: 99%
“…These AEs can significantly lower compliance, sometimes leading to discontinuation before a therapeutic effect can be achieved. In patients in whom insufficient efficacy is observed with pregabalin, switching to other agents has been studied, and a reduction in AEs and an improvement in pain relief have been reported [12]. Thus, when considering a switch from pregabalin to mirogabalin, safety is an important consideration; however, there are insufficient safety data available in this setting.…”
Section: Introductionmentioning
confidence: 99%
“…A Cochrane review of pregabalin reported that the withdrawal rate due to AEs was 3.6%-19% and that due to all causes was 12%-26% when pregabalin was administered at a dose of 600 mg daily 3) . There have been a few reports of PNeP treatment wherein pregabalin could not be administered continuously [4][5][6] , and it remains unclear which drug should be administered following this discontinuation.…”
Section: Introductionmentioning
confidence: 99%